1998
DOI: 10.1021/jp972499y
|View full text |Cite
|
Sign up to set email alerts
|

Dynamics of Excited Solvated Electrons in Aqueous Solution Monitored with Femtosecond-Time and Polarization Resolution

Abstract: Transient pump−probe spectroscopy of equilibrated solvated electrons is carried out in aqueous NaCl solution (5.9 M) in the visible and near-infrared using pulses of 100−170 fs duration and polarization resolution. Excitation is performed by a pump pulse at 620 nm in the blue wing of the electronic absorption band. Transient bleaching occurs in a broad interval around the maximum of the e- absorption at 705 nm, accompanied by induced absorption at longer wavelengths. No hole-burning features are observed withi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
117
1

Year Published

1998
1998
2007
2007

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 87 publications
(122 citation statements)
references
References 47 publications
4
117
1
Order By: Relevance
“…Their later experiments were interpreted in terms of a ~300 fs solvent relaxation in the 2p-excited state followed by a NA decay with a time constant around 1 ps. 57,58 More recent work by Assel et al, 59,60 supported the former scenario. Very recently Pshenichnikov et al 61 have performed photon-echo experiments with very short (5 fs) pulses and they have concluded that the p-state lifetime should be much shorter than stated before, ~50 fs, with an (expected) 2 kinetic isotope effect in heavy water.…”
Section: Introductionmentioning
confidence: 79%
See 1 more Smart Citation
“…Their later experiments were interpreted in terms of a ~300 fs solvent relaxation in the 2p-excited state followed by a NA decay with a time constant around 1 ps. 57,58 More recent work by Assel et al, 59,60 supported the former scenario. Very recently Pshenichnikov et al 61 have performed photon-echo experiments with very short (5 fs) pulses and they have concluded that the p-state lifetime should be much shorter than stated before, ~50 fs, with an (expected) 2 kinetic isotope effect in heavy water.…”
Section: Introductionmentioning
confidence: 79%
“…For this reason the solvated electron has been considered as a sensitive probe and model of solvation dynamics, and has been the subject of several theoretical 3,[5][6][7][8][9][10] and experimental studies. [52][53][54][55][56][57][58][59][60][61][62][63] Within our modified golden rule formula, we wish to calculate the classical decay rates, and compare them to the quantum transition rate obtained by quantizing the classical TCF's. This comparison may shed light on the contributions of the different nuclear modes, and clarify the applicability of the presently employed quantization schemes to the solvated electron relaxation problem.…”
Section: Introductionmentioning
confidence: 99%
“…3 Another, more controversial issue is the interpretation of pump-probe excitation experiments in terms of the contributions of ground and excited state solvent reorganization dynamics and excited state population decay. 4,5,6,7,8,9,10 We focus on this issue of excited state lifetime in the present work.…”
Section: Introductionmentioning
confidence: 99%
“…Equally important is the structural response of the solvent environment since the mutual interaction between solvent and solute can influence the reaction dynamics. Recent attempts to address this issue using femtosecond optical pulses have focused on the solvated electron as a model probe of the solvent environment [97][98][99][100][101][102]. Analysis of the transient absorption and dephasing provide information about the statistical fluctuations of the solvent, but cannot provide any direct structural information.…”
Section: Solvent-solute Structural Dynamicsmentioning
confidence: 99%